PENINGKATAN PERILAKU SOPAN MELALUI METODE BERCERITA PADA ANAK 5 â€“ 6 TAHUNDI TK SUSTER PONTIANAK - Valentina, Valentina; Syukri, M.; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn general, the purpose of this study is to determine the success of teachers improve the quality of learning process using storytelling method to improve the development of polite behavior in children aged 5-6 years in kindergarten Sister Pontianak.Penelitian this research using Class Action Research, which is one of the problem solving strategy utilizing real action and capacity building process in detecting and solving problems. Based on the result of data analysis and research question in general can be concluded that learning using story telling method can improve the behavior of courtesy in children aged 5-6 years in kindergarten Sister Pontianak. It is based on the result of learning planning made by teachers to improve the behavior of children's manners reached the category of 'Good' with a score of 3.57. Implementation of learning conducted by teachers in improving the behavior of children's behavior through the method of telling stories reached the category of "Good" with a score of 3.35. The storytelling method applied by teachers in learning can improve the behavior of children's manners this is shown by 97% children develop as expected.Â Keywords: Sopan Santun, Method of Storytelling